Labour Economics : Principles Problems and Practices - Jiwitesh Kumar Singh (New Delhi Regal Publications, 2022)
Labour Economics; Labour market issues; Trade unionism; Industrial Relations; Wages payment policy and methods; Social security and international Labour organization.
Keywords: Labour Economics